Mobile Based Application Design of Management System “Travel Budget” Using Flutter - Maziya Azelicha Ayana; Suwarno Liang (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Nowadays, many people participate in traveling as their preferred leisure activity. When traveling, unexpected circumstances can arise, including changes in travel plans, unforeseen expenses, medical costs, or alterations to meal plans, which may require additional budgeting. Recording expenses during a trip allows travelers to allocate their budget effectively for transportation, food, lodging, tourist activities, and other expenses. To solve this problem, this study aims to design a mobile management system called "Travel Budget" using Flutter to assist users in recording their travel expenses while visiting a specific country. Both the qualitative method and the Research and Development (R&D) method using the 4D approach will be used in this study. With this research, it is hoped that it can bring benefits to the travelers who need to track their expenses, increase the knowledge of the public and readers about mobile based application, and become a reference for the next research.